Densification and Combustion Studies of Empty Fruit Bunch and Napier Grass for Pellet Production - V’shnu Nair, Kamesh (IRC, 2017)
Due to demand in our daily lives, alternative energy for fossil fuel has to be discovered to be able to support the demand of energy. In many alternative energy that is being produced, biomass energy is one of the popular choices around. This is due to it being environmental friendly, cheap and is found in abundance. This report shows the study of the potential of using two biomass material, empty fruit bunch and Napier grass to produce pellet for energy production. The problem that is encountered is that being individual materials, these both exhibit good burning properties but requires high amount of work. Hence, it was both then combined to act as a binding agent for each other to increase the pellets density. Pellets was made at different weight ratio and will be tested for densification and combustion properties using compression machine at 10kN for 10 minutes. Densification properties will include maximum density, relaxed density, durability, compressive strength and surface morphology. Combustions or energy properties will include higher heating value, moisture content, and FTIR spectrum analysis. Based on the properties, all the pellets exhibited good properties such as having durability above 95%, moisture content below 15%, density above 0.650g/cm3 and reasonable HHV which indicated the pellets was acceptable for its properties based on comparison with literature reviews. SEM images also further supported the properties exhibited by the pellets as the significance of values was explained due to the binding strength of molecules within the pellets. Pellet B (75%-25%) EFB-Napier was the best pellet as the HHV value was close to 17000 J/g, the highest among all the 5 pellets. The study was concluded to show the properties that is exhibited by the pellets and hence pellet B with ratio of 75%-25% EFB-Napier was the best ratio for obtaining mixture of biomass pellet comprising of these two material